- - - Wu, Bingrui (Journal of Medical Biochemistry, 2025)
Objective: To explore how Baoyuan and Taohong Siwu decoctions combined with western medicine affect triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) in elderly patients with coronary heart disease. Methods: 90 elderly patients with coronary heart disease who were hospitalized from January 2021 to December 2022 were selected and divided into two groups based on different treatment methods, with 45 patients in each group. The control group was treated with western medicine alone, while the research group was treated with Baoyuan and Taohong Siwu decoctions in combination on the basis of control group. The improvement of traditional Chinese medicine symptom scores, various blood lipid levels, and serum indicators of cardiac function were compared between two groups before treatment, 1 month, 2 months, and 3 months of treatment. Results Before treatment, two groups had same Traditional Chinese Medicine symptom scores, various blood lipid levels, and various serum indicators of cardiac function (P>0.05). After treating 1 month, 2 months, and 3 months, the scores of chest pain, chest tightness, fatigue, and sweating in the research group were lower (P<0.05). The TG, TC, LDL-C, and HDL-C levels in the research group were lower (P<0.05). The levels of plasma N-terminal brain natriuretic peptide (NT-proBNP) and monocyte chemoattractant protein-1 (MCP-1) in the research group were lower (P<0.05). Conclusion The combination of Baoyuan and Taohong Siwu decoctions and western medicine treatment can help improve elderly coronary heart disease’s symptoms and signs. It can reduce the levels of various indicators such as LDL-C, TG, TC, and HDL-C in the body, and promote the improvement of cardiac function.